M38 Health Professionals' Views Of Tuberculosis Cohort Audit In North West England. (10th November 2014) - Wallis, S; Jehan, K; Woodhead, M; Cleary, P; Dee, K; Farrow, S; McMaster, P; Wake, C; Walker, J; Squire, SB
Abstract : Introduction and objectives: Tuberculosis cohort audit (TBCA) was introduced across the North West in 2012 as recommended by NICE. The approach taken and the outcome measures of the 1, 515 TB cases reviewed are presented in a companion abstract. TBCA over a large geographical area has not undergone formal qualitative evaluation in the UK. We conducted a qualitative evaluation to explore perceptions about implementation and impact of TBCA in the North West. Methods: One researcher conducted face to face, semi-structured, recorded interviews between 06/01/14 and14/03/14 with 26 purposively sampled respondents from three groups involved in TBCA: (a) TB nurse specialists; (b) Consultant physicians; (c) Public health practitioners. Transcripts were analysed descriptively and thematically using the Framework Method. Themes were triangulated with eight key informants from the TBCA Steering Group. Results: Four themes were identified: Preconceptions: Participants were optimistic about the potential of audit to improve practice but worried about time demands and scrutiny from colleagues. Experience of TBCA: All groups felt engaged and appreciated TBCA. Nurses requested more engagement from consultant colleagues. Fears about time demands and scrutiny were not realised. Changes as a result of TBCA : Improvements to practice were identified including harmonisation of approaches, increased HIV testing, and improved documentation. TBCA was felt to provide peer support and learning through discussion and a no-blame atmosphere. Looking Ahead: Suggestionsfor further improvement were captured, such as more in-depth discussion around complex cases. If TBCA were to be discontinued (e.g. because of funding contraints), adverse consequences were predicted: e.g. disappointed and disenfranchised professionals, financial and patient harms. Conclusions: Overall, TBCA in the North West has led to the development of a unique and valuable community of practice. The interchange of experience and ideas across a large number of teams and professionals has enhanced mutual respect between different roles and a shared sense of purpose. TBCA is appreciated by health professionals who participate. Continuing success will require increased engagement of consultant physicians and public health practitioners, a secure an ongoing funding stream and establishment of reporting mechanisms within the new commissioning structures.